2016
DOI: 10.1016/j.egja.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding dexmedetomidine to local anesthetic mixture for peribulbar block in vitreoretinal surgeries

Abstract: The purpose of this study was to compare the effect of adding different doses of dexmedetomidine to local anesthetic mixture for peribulbar block in vitreoretinal surgeries as regards duration, efficacy and pain relief. Materials and methods: In this prospective randomized double blind clinical study, 160 patients were equally divided into four groups: Group C (the control group) (n = 40) received 10 ml mixture of lidocaine 2% and bupivacaine 0.5% with 120 IU of hyaluronidase, group D15 (n = 40) received a 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
5
8
2
Order By: Relevance
“…This study in agreement with the results of Hafez et al [18] who evaluated the effect of three doses of dexmedetomidine 15 mg, 20 mg, 25 mg when added to a mixture of lidocaine 2%, bupivacaine 0.5%, and 120 IU of hyaluronidase for peribulbar anesthesia in vitreoretinal surgeries on 160 patients and they found that dexmedetomidine accelerated onset of sensory and motor block and increased its duration and the analgesia time. They found that the best dose was 25 mg dexmedetomidine.…”
Section: Discussionsupporting
confidence: 92%
“…This study in agreement with the results of Hafez et al [18] who evaluated the effect of three doses of dexmedetomidine 15 mg, 20 mg, 25 mg when added to a mixture of lidocaine 2%, bupivacaine 0.5%, and 120 IU of hyaluronidase for peribulbar anesthesia in vitreoretinal surgeries on 160 patients and they found that dexmedetomidine accelerated onset of sensory and motor block and increased its duration and the analgesia time. They found that the best dose was 25 mg dexmedetomidine.…”
Section: Discussionsupporting
confidence: 92%
“…this could be explained by that dexemedtomidine in these studies was given either parentrally or neuroaxilally resulting in a central action by decreasing the sympathetic outflow and norepinephrine release. While our results were similar to Hafez M et al [38] study who failed to find any statically significant effects of peribulbar dexemedtomidine on haemodymaics.…”
Section: Discussionsupporting
confidence: 68%
“…This is in contrary to Hafez et al [38] who found no significant effect to Dexmedetomidine addition in different doses on VAS score when compared to the control group.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations